Impact Analysis of Vehicle Load and Average Daily Traffic on Damage to Siliwangi Highway Roads Bekasi STA 0+000 - 1+800 Using SPSS and AASHTO Method - Sandiawan, Falco; Sari, Ribut Nawang; Choiri, Aulia; Artanti, Lintang Dian (Journal of Global Engineering Research and Science, 2023)
The damage on the Siliwangi Bekasi road is suspected to be caused by the large number of heavy vehicles passing through the road. The purpose of this study was to analyze the effect of daily traffic and vehicle load on the damage to Jalan Raya Siliwangi Bekasi. From thr calculation in this study, we can know that the Truck Factor value on the Siliwangi road from the Narogong direction to the Cut Meutia direction is 4.008 which is larger than 1 and truck factor value on the Siliwangi road from the direction of Cut Meutia to the direction of Narogong is 4.403 which is larger than 1. This indicates that road damage is caused by traffic load factors. Based on the results of the R Square test R Square value is 0.539 and 0.924, thus it can be said that daily traffic affects road damage by 53.9% and 92.4%. Based on the results of the t test between vehicle volume and road damage on highway Siliwangi Bekasi from Narogong to Cut Meutia road it is known that: The calculated t value of vehicle volume is 2,858 with Sig 0.024 and the other road section is 6,965 with Sig 0.02 we can conclude that the vehicle volume is greater than t table and the significant level of t calculated vehicle volume is less than 0.05, it can be interpreted that vehicle volume has a significant effect on road damage.